Physiopathology of essential arterial hypertension Raúl Gamboa A1 - Gamboa A, Raúl (2006)
Arterial hypertension has a high prevalence in modern society and despite the great advances in our knowledge of its mechanism, the impact of its control is poor general. Although this complex mechanism interact, the method more frequently used of its treatment is the essay error consider phenotype variables as result of interaction of environmental genotype and respect of basic conditions such as a) effectivity, b) with out harming the quality of life, c) without propitiating the development of factors of risk d) without oppositions with the co-morbidity and e) directed to the protection of the organs target. Treatment ideally of essential hypertension patient should base on the physiopathologic mechanisms knowledge that contributes to its development. The current genetic and human genome advances integrates of physiologic and physiopathologic knowledge and population researches led us in the future reach a more selective and rational treatment even the arterial hypertension prevention.